STRATEGI PEMASARAN BOKAR DI KECAMATAN KAMPAR KABUPATENKAMPAR - Ihsannul hakim; Yeni Kusumawaty; Shorea Khaswarina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Marketing system of these rubber commodities in the district mines has not been well-organized, because it was still through an intermediary institution.The purpose of this research is to formulate a marketing strategy for the marketing of rubber can be more efficient. Analysis of the data for this research uses a descriptive qualitative analysis and stage strategies, which are matrix IFE, EFE and SWOT matrix. The data retrieval process is done with observation and interviews. The results showed that there were from the results of IFE matrix and EFE obtained score of 2.425and3.257. The recommendations for the formulation of the rubber marketing strategy obtained from the results of the SWOT analysis are (i) The government has established a bokar marketing institution that has a role in facilitating the quality of bokar reservoirs and facilitates the marketing of bokar to factories in accordance with factory demand. (ii) Strengthening capital for marketing activities of farmer groups through collaboration between farmer groups and BUMDes. (iii) Collaboration between rubber farmers or farmer groups by forming bokar storage centers or warehouses aimed at storing. (iv) Facilitation of partnership patterns between factories and rubber farmers through farmer groups by the Government.Keywords: Bokar, Bokar MarketingStrategy